Disinfectant and Antimicrobial Susceptibility Profiles of Campylobacter coli Isolated in 1998 to 1999 and 2015 from Swine and Commercial Pork Chops. Issue 6 (22nd May 2019) - Beier, Ross C.; Harvey, Roger B.; Hernandez, Charles A.; Andrews, Kathleen; Droleskey, Robert E.; Hume, Michael E.; Davidson, Maureen K.; Bodeis‐Jones, Sonya; Young, Shenia; Anderson, Robin C.; Nisbet, David J.
Abstract : Abstract: Susceptibility profiles were determined for 111 Campylobacter coli strains obtained in 1998 to 1999 and 2015 from market age pigs and pork chops against 22 disinfectants and 9 antimicrobials. Resistance to tetracycline (TET) was observed in 44.4% of 1998 to 1999 strains, and the antibiotic resistance profile was TET. But strains obtained in 2015 from swine and retail pork chops had 75% TET resistance and the antibiotic resistance profile was TET, followed by azithromycin‐erythromycin‐TET‐telithromycin‐clindamycin. Antimicrobial resistance increased in 2015 strains. All strains were resistant to triclosan, and 84.1% and 95.8% of strains in 1998 to 1999 and 2015, respectively, were chlorhexidine resistant. All strains were susceptible to benzalkonium chloride. There was a shift toward higher susceptibility to chlorhexidine, triclosan, P‐128, OdoBan, CPB, and CPC in 2015 swine and pork chop strains compared with 1998 to 1999 strains. The disinfectants Tek‐Trol and providone‐iodine, tris(hydroxylmethyl)nitromethane (THN) and formaldehyde demonstrated the highest susceptibilities. Didecyldimethylammonium chloride (C10AC) appeared to be about equally effective as benzyldimethyltetradecylammonium chloride (C14BAC) for inhibiting C. coli, and both were more effective than C8AC and C12BAC, but C16BAC was not efficient at inhibiting C. coli . The BACs, C12BAC and C14BAC, were the most effective ingredients in DC&R. Also, C12BAC and C14BAC, or these two in synergy with C10AC were responsible for inhibition of C. coli at high P‐128 MICs. No cross‐resistance was observed between antibiotics and disinfectants. The continued use of THN and formaldehyde in DC&R should be evaluated since these components are not effective, and their inclusion adds unwanted chemicals in the environment. Practical Application: Campylobacter species cause diarrheal disease throughout the world. Disinfectants are often used on the farm, in veterinary medicine, by the food processing industry, in restaurants, and in consumer's homes. Limited information is available in the literature showing how disinfectants or disinfectant components may affect the many different foodborne pathogens, and, specifically, Campylobacter coli studied here. The knowledge generated in this study concerning the interactions of a broad array of disinfectants against C. coli may well affect the types of disinfectants and disinfectant formulations allowable for use by medical personnel, producers, food processors, restaurants, and consumers.